Myosin 1g and 1f: A Prospective Analysis in NK Cell Functions - Cruz-Zárate, David; Miguel-Rodríguez, Carlos Emilio; Martínez-Vargas, Irving Ulises; Santos-Argumedo, Leopoldo (Frontiers in Immunology, 2021)
NK cells are contained in the ILC1 group; they are recognized for their antiviral and antitumor cytotoxic capacity; NK cells also participate in other immune response processes through cytokines secretion. However, the mechanisms that regulate these functions are poorly understood since NK cells are not as abundant as other lymphocytes, which has made them difficult to study. Using public databases, we identified that NK cells express mRNA encoding class I myosins, among which Myosin 1g and Myosin 1f are prominent. Therefore, this mini-review aims to generate a model of the probable participation of Myosin 1g and 1f in NK cells, based on information reported about the function of these myosins in other leukocytes.